2022
DOI: 10.3390/ijms23020769
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Goldenrod, Milkweed and Multifloral Honeys Based on Botanical Origin, Antioxidant Capacity and Mineral Content

Abstract: The goal of the study was to evaluate the pollen spectrum, antioxidant capacity and mineral content of four Hungarian honey types, using multivariate statistical analysis. The light colored honeys were represented by milkweed honey and a multifloral (MF) honey with dominant pollen frequency of linden (MF-Tilia); the darker ones were goldenrod honey and a multifloral honey with Lamiaceae pollen majority (MF-Lamiaceae). The pollen spectrum of the samples was established with melissopalynological analysis. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
7
7
0
Order By: Relevance
“…A major strength of our study is the extensive assessment of selected European honey types, focusing not only on identification traits (color, sensory characteristics, pollen spectrum) and quality parameters (antioxidant capacity, mineral content), but also establishing a connection with their antibacterial and antibiofilm effects. Our current study confirmed the reliable quality parameters of linden, milkweed, goldenrod and chestnut honeys, supporting our previous observations ( 1 , 9 ). As a starting point we selected the current honey samples based on the general observation that the color, antioxidant capacity and mineral content of honey were in positive correlation ( 1 , 9 , 46 48 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A major strength of our study is the extensive assessment of selected European honey types, focusing not only on identification traits (color, sensory characteristics, pollen spectrum) and quality parameters (antioxidant capacity, mineral content), but also establishing a connection with their antibacterial and antibiofilm effects. Our current study confirmed the reliable quality parameters of linden, milkweed, goldenrod and chestnut honeys, supporting our previous observations ( 1 , 9 ). As a starting point we selected the current honey samples based on the general observation that the color, antioxidant capacity and mineral content of honey were in positive correlation ( 1 , 9 , 46 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our current study confirmed the reliable quality parameters of linden, milkweed, goldenrod and chestnut honeys, supporting our previous observations ( 1 , 9 ). As a starting point we selected the current honey samples based on the general observation that the color, antioxidant capacity and mineral content of honey were in positive correlation ( 1 , 9 , 46 48 ). In our case, the light colored linden honey was an exception with low TRC and TEAC, but high ORAC and mineral content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, in the present study, the color of Polish honey samples was the lightest, compared to Slovakian and Hungarian goldenrod honeys. In accordance with several other studies examining the relationship between honey color and antioxidant capacity [ 31 , 32 , 34 , 35 , 36 , 37 , 38 ], we found that color intensity correlated with total polyphenolic, flavonoid, and phenolic acid content, as well as antioxidant activities.…”
Section: Discussionsupporting
confidence: 92%
“…Goldenrod honeys from more southern locations (Hungary) exhibited higher antioxidant activity than the Polish and Slovak ones with the northernmost origin. Microclimatic differences may contribute to increased total polyphenolic content, which, in turn, influences antioxidant potential [ 32 ].…”
Section: Discussionmentioning
confidence: 99%